The Contribution of Guides In Promoting The Tourist Product - Farangiz Azimova Madina Yakubova (European Journal of Life Safety and Stability (2660-9630), 2023)
The aim of this study is to determine the role and significance of a tourist guide as an intermediary between supply and demand and as well as their role in providing a bridge between tourists and local communities in supporting the local economy and sustainable tourism within tourist destinations. Research on tourism suggests that tourist guides are key representatives in the tourism industry in that they have contributed significantly to the satisfaction of visitors and are believed to determine whether or not the tourist will revisit destinations. The present study sought to investigate the perception of local tour guides pertaining to their future carrier as tour guides and the roles they played in the profession. It also assessed the perceived learning needs as tour guides. In today’s international tourism, culture and traditions are important parts for many destinations because they are a means of their national identity promotion. Without guides and their role, it may happen that current resources or even important information can not be available to visitors or isn’t properly understood by them. Intercultural communication and interpretation of local cultural heritage, values living culture and cultural identity in general are main components of the actual guide’s role. Unlike any other tourism actors tourist guides are front-line professionals who, unlike any other tourism actors establish a close, intense and influencing contact with visitors while at the same time protects interests of sustainable cultural tourism. Their profession is commonly accepted as an uninspiring repetitive, and mass tourism activity. It can be a creative and effective tool in the construction of tourist experiences.